WEBVTT
00:00:00.980 --> 00:00:07.040
Simplify root three plus two multiplied by root three minus two.
00:00:08.820 --> 00:00:15.460
We notice that this expression is written in the form 𝑥 plus 𝑦 multiplied by 𝑥 minus 𝑦.
00:00:16.370 --> 00:00:22.520
Using our difference of two squares result, this is equal to 𝑥 squared minus 𝑦 squared.
00:00:24.000 --> 00:00:28.860
Our value for 𝑥 is root three, and our value for 𝑦 is two.
00:00:29.890 --> 00:00:34.010
𝑥 squared would therefore be equal to root three squared.
00:00:35.020 --> 00:00:39.210
We know that square routing and squaring are inverse operations.
00:00:39.450 --> 00:00:42.070
Therefore, 𝑥 squared is equal to three.
00:00:43.410 --> 00:00:48.530
𝑦 squared is equal to four as two multiplied by two is four.
00:00:50.180 --> 00:00:57.650
The expression root three plus two multiplied by root three minus two is equal to three minus four.
00:00:58.850 --> 00:01:01.290
This is equal to negative one.